Arabic Grammar: The History of Its Emergence and the Most Prominent Grammarians - hindun hindun (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2020)
The science of grammar is one of the highest sciences and the most beneficial. It has a strong relationship and connection to learning Arabic language skills. To make it easier to learn and understand grammar without much difficulty is to know and learn its history. When a student has studied its history, it becomes easier for him to learn hard and many rules are hidden for him. From this point of view, the researcher tried to clarify the history of grammar and what transforms what grammar is, the reason for its inception, its setting, and a simple explanation of the emergence of grammar and the history of the most famous grammarians. The approach followed is the descriptive and analytical approach and the most important results of the research are: First, the reason for the emergence of grammar is the spread of melody and errors in pronunciation in general and the pronunciation of the Qur’an in particular, secondly the emergence of grammar is four phases, thirdly the two famous doctrines are Kufa and Basra